2014
DOI: 10.1111/hex.12186
|View full text |Cite
|
Sign up to set email alerts
|

Patient participation in clinical encounters: a systematic review to identify self‐report measures

Abstract: Background There is evidence suggesting that active participation of patients in their health care can improve the quality of care and decrease health-care costs. Further, patient reports of their healthcare experience are increasingly used to monitor health-care quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Notably, OPTION 5 Item 2, which assesses whether a clinician has explained the need to deliberate about treatment options and supports the patient to become informed, also received low scores. Although this finding is surprising in light of the high-level of proficiency in presenting information about the available options, this again reflects the lack of understanding one of the core principles of SDMnon-abandonment of patients as they are asked to become active participants in their health care, a role unfamiliar to many patients [31][32][33]. It is important to note that clinician 4, a gastroenterologist who achieved consistently high scores on all SDM competencies, is particularly well versed in SDM, has developed his own tools, seminars and workshops, and is leading a number of clinical research initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, OPTION 5 Item 2, which assesses whether a clinician has explained the need to deliberate about treatment options and supports the patient to become informed, also received low scores. Although this finding is surprising in light of the high-level of proficiency in presenting information about the available options, this again reflects the lack of understanding one of the core principles of SDMnon-abandonment of patients as they are asked to become active participants in their health care, a role unfamiliar to many patients [31][32][33]. It is important to note that clinician 4, a gastroenterologist who achieved consistently high scores on all SDM competencies, is particularly well versed in SDM, has developed his own tools, seminars and workshops, and is leading a number of clinical research initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…16 In another systematic review to find measures of patient's active participation in encounters with health care, three conceptual frameworks were identified as empowerment and self-efficacy, therapeutic alliance and satisfaction. 17 Additionally, to look for evidence on the effects of use of services, quality of care and health of patients has been underlined. 18 Patient organizations and primary care development, Berglund Strategies and routines for how to cooperate between authorities and organizations for the public good are needed in the society.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 39 relevant reviews 20,40,[66][67][68][69] and 35 primary studies or discussion papers. 17,40,67,83,[93][94][95][96][97][98][99][100][101][102] Information extracted from the reviews included study aims, types of participants, definition of SDM, outcomes measured, relevance to our target group and any theoretical assumptions made. The reviews allowed us to understand the range and approach of research on SDM but provided limited detail with which to develop our programme theory.…”
Section: Scoping the Literaturementioning
confidence: 99%
“…Although many SDM initiatives involve giving patients more information, this alone is not enough; patients need knowledge and power to participate in SDM. 102,116 A systematic review of patient-reported barriers to, and facilitators of, SDM suggested that power may be linked to perceptions of permission to participate in decision-making, perceived influence on decision-making, confidence in own knowledge and self-efficacy in SDM. 116 Outcomes A systematic review of tools to promote SDM in serious illness suggested that decision aids have the potential to reduce health-care intensity and costs by decreasing unwanted major high-cost interventions or hospitalisations but that these outcomes have not been studied.…”
Section: Patient Activation or Engagementmentioning
confidence: 99%